2021
DOI: 10.1186/s12969-021-00554-w
|View full text |Cite
|
Sign up to set email alerts
|

Age, gender, height and weight in relation to joint cartilage thickness among school-aged children from ultrasonographic measurement

Abstract: Background Among school-age children, the decrease of cartilage thickness (Cth) with increasing age is well known. However, the influence of body mass index (BMI), height or weight on Cth has not been revealed. Here in, we aim to establish an age- and gender-specific Cth standard reference among Asians and investigate the possible prestige of BMI, height and weight. Methods A cross-sectional study was performed in healthy Asian children. Bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In healthy children, cartilage thickness in the knee differs significantly between sexes, with girls having thinner cartilage than boys [ 14 , 15 ]. Weight, height, and body mass index (BMI) contribute to cartilage thickness, but age is the leading contributor among school age children [ 14 ]. Physical activity benefits tibial cartilage volume [ 16 ].…”
Section: Sex Differences In Knee Anatomy and Cartilage Degenerationmentioning
confidence: 99%
“…In healthy children, cartilage thickness in the knee differs significantly between sexes, with girls having thinner cartilage than boys [ 14 , 15 ]. Weight, height, and body mass index (BMI) contribute to cartilage thickness, but age is the leading contributor among school age children [ 14 ]. Physical activity benefits tibial cartilage volume [ 16 ].…”
Section: Sex Differences In Knee Anatomy and Cartilage Degenerationmentioning
confidence: 99%
“…Fluorescent images in Figure 3a show that after 24 h of exposure, the BPL molecules penetrated further into the cartilage tissue; that is, we found a penetration depth for G0, G1, and G2 BPL molecules of 1550 ± 50 μm, 1710 ± 30 μm, and 1620 ± 25 μm, respectively (Figure 3c). These results suggest that despite the changes in molecular architecture (i.e., branching, PEGylation) and surface charge, all of the different BPL molecules significantly penetrated into the cartilage explant by 24 h; that is, to depths that are on the same order of magnitude as human cartilage tissue thickness 21–23 …”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that despite the changes in molecular architecture (i.e., branching, PEGylation) and surface charge, all of the different BPL molecules significantly penetrated into the cartilage explant by 24 h; that is, to depths that are on the same order of magnitude as human cartilage tissue thickness. [21][22][23] To further characterize the electrostatic interactions between the negatively charged cartilage ECM and the positively charged BPL molecules, we performed a desorption assay by incubating the BPL-absorbed cartilage explants in 1Â or 10Â phosphate buffered saline (PBS) and measuring the amount of BPL molecules released into the solution as a function of time for up to 4 days. The results showed that around $20% of G0 BPL molecules and 10%-15% of all other BPL molecules, including the PEGylated G1 and G2 molecules, were desorbed from the cartilage explants in 1Â PBS after 4 days (Figure 4a-c).…”
Section: Cartilage Uptake Penetration and Retention Of Bpl Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of mechanical stress and physical activity on the thickness and volume of cartilage has been subject of research for decades [3,9,15,20,29,38,47]. The effect and influence of sex, growth, weight and body composition on the thickness of the articular cartilage in school-aged children has been reported in several studies [12,19,30,41].…”
Section: Introductionmentioning
confidence: 99%